THE ROLE OF THE EDITOR IN MAKING PROMOTIONAL VIDEOS FOR MERAPI TURGO TOURISM - Ramadhana, Muhammad Fikri; Pudrianisa, Sheila Lestari Giza (JURNAL SOCIUS, 2024)
Tourist villages are a forum for village communities to develop tourism products because they have various potentials in terms of nature, food and culture as the identity of tourist attractions. One of them is the Merapi Turgo Tourism Village which is located on the slopes of Mount Merapi, Padukuhan Turgo, Purwobinangun Village, Pakem District, Sleman Regency, Yogyakarta. The village has various tourism potentials. However, the lack of good management and promotion has made the village little known. The problems faced make it difficult for the village to develop, especially in getting investors. So from the results of observations, researchers discovered the fact that one way to overcome this is through making promotional videos, because online media currently dominates various forms of effective marketing. In making promotional videos, an important role is needed from a team of experts in their fields, both in the pre-production, production and post-production processes. One of the crucial roles is the Editor because in making a film or video, the cameraman's shooting process is still not structured so the role of the editor in post-production is very necessary to package tourism promotional videos more attractively. Editors at Turgo Tourism Village in making Tourism Promotion Videos use editing techniques such as cutting, light leak zoom in and zoom out transitions, fading, appropriate motion graphics, adjusted color grading so that the video results are better. interestingly, the author uses Adobe Premiere Pro software because this software has many features that help the author in the video editing process.